Green Innovation And Organizational Culture Toward Corporate Value: Moderation Role Of Competitive Advantage - Suyono, Suyono; Murwaningsari, Etty (LPPM ISNJ Bengkalis, 2024)
The study aims to analyze the impact of green innovation and organizational culture on corporate value and competitive business strategy as moderating variables. This type of research is quantitative, with secondary data sources. During the 2016–2020 period, the population of this study consisted of 74 energy sector companies. Purposive sampling, the chosen sampling technique, yielded a total sample of 53 energy sector companies. The technique for collecting data involves accessing financial report documentation from the Indonesian Stock Exchange website. The SPSS program facilitates the data analysis technique, which employs descriptive analysis and regression with moderation effects. The research results show that green product innovation, hierarchical culture, clan culture, and competitive business strategy do not affect corporate value. The competitive business strategy strengthens the influence of product innovation and organizational culture on corporate value in the energy sector. Theoretically, this research can complement the factors influencing corporate value through the moderating role of competitive business strategy. This research can be a practical reference and illustration for companies considering competitive business strategy factors.